The effect of inventory intensity, capital intensity, and leverage on tax avoidance - Yunira, Haervi; Lubis, Citra Windi; Lubis, Nurul Izzah; Khairunnisa, Khairunnisa (Institute of Computer Science (IOCS), 2025)
The objective of this research is to examine the impact of inventory intensity, capital intensity, and leverage Regarding tax avoidance among food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2019–2023 period. The research adopts a quantitative method utilizing multiple linear regression analysis. The findings indicate that capital intensity Exhibits a positive and significant influence on tax avoidance, whereas inventory intensity and leverage do not Have a significant impact. At the same time. Concurrently, these variables are not found to significantly influence tax avoidance.